Normen und Standards für die digitale Transformation Werkzeuge, Praxisbeispiele und Entscheidungshilfen für innovative Unternehmen, Normungsorganisationen und politische Entscheidungsträger - Mangelsdorf, Axel; Weiler, Petra (De Gruyter, 2019)
Norms and standards are indispensable for the success of the economy's digital transformation, even as their applications become more and more complex. This book sheds light on relevant findings from standards research, participation in standardization consortia, certification, and other important aspects and condenses them into specific recommendations.